Reflections on Indigenous Cosmopolitics—Poetics - Poirier, Sylvie (Anthropologica, 2022)
This article is intended as an exploration into what I call indigenous cosmopolitics-poetics, in the metaphysical sense of the politics of the cosmos, and as an attempt to draw a parallel between these cosmopolitics and recent anthropological work on "relational ontology." Among the expressions of contemporary indigenous cosmopolitics, I explore: the notion of the person as "dividual" and of the self as "relational"; the concept of ancestrality; and translocal networks of ritual exchanges and gatherings. To explore these avenues, I draw from my work and experiences with two indigenous groups, namely the Kukatja (Australian Western Desert) and the Atikamekw (North-Central Quebec).